THE HISTORICAL AND CONTEMPORARY MACEDONIAN PARADOXES THE CASE OF VENKO MARKOVSKI (Annual of the Faculty of Philosophy in Skopje, 2009)
In this article we are analize the separate aspects of the character ofVenko Markovski, the first contemporary Macedonian poet, the member in theNational-Liberation War, the supporter of Stalin and the national dissident.Because of the subject and the several difficult explanations about the characterof Markovski, we will write only about the so called Macedonian chapter ofhis activities. We will write only about his membership in the National-LiberationWar, until his immigration in Republic of Bulgaria. We will try to explain,what is the reason of the transformation of Venko Markovski.
Keywords: AUTHONOMISM; SEPARATISM; IDENTITY; DISSIDENT; STALINISM; MIGRATION; YUGOSLAVIAN IDEA